Do clerkship schemes effectively improve pharmacy students’ understanding of and attitudes regarding pharmaceutical care?——a pre-post study in China Pharmaceutical University - Yuankai Huang; Dongning Yao; Weiwei Zhang; Yitao Wang; Wenbing Yao (BMC Medical Education, 2019)
Abstract Background Clerkship is potentially an effective measure of improving the pharmacy students’ understanding of and attitudes toward pharmaceutical care. This research aimed to validate whether clerkship schemes in China effectively improve pharmacy students’ understanding of and attitudes toward PC, and discuss on how to improve the clerkship schemes for better quality. Methods A pre-post and self-administrated questionnaire survey among three continuous years of students was conducted to measure Chinese fifth-year clinical pharmacy students’ differences in understanding of pharmaceutical care and attitudes toward pharmaceutical care before and after their clerkship schemes. Statistical analysis was conducted on the retrieved data. Results 602 respondents completed the post-part survey (drop rate = 1.8%). Correct rates of all statements regarding students’ understanding of pharmaceutical care were generally increased, but the rates of respondents holding correct understanding of the primary goal of pharmaceutical care (71.9 to 85.0%), the necessity of drug information support in pharmaceutical care (77.1 to 87.5%) and the patients’ role and duty when receiving pharmaceutical care (66.1 to 70.6%) were unsatisfactory before the clerkship and the improvement was not significant. Most statements regarding students’ attitudes toward pharmaceutical care were improved in general. However, rates of respondents holding negative attitudes toward students performing pharmaceutical care during their clerkship (3.7 to 7.5%) and choosing pharmaceutical care provider as their career after clerkship schemes (10.8 to 14.8%) had increased after the clerkship schemes. Conclusion Clerkship generally improves clinical pharmacy students’ understanding of and attitudes toward pharmaceutical care, yet adjustments are also required in some contents of the clerkship for further improvements in its outcomes.